Anthropocene - Draper, Jamie (Wiley, 2022)
The “Anthropocene” is a term used to mark a period of history where humans have become the dominant force in the transformation of the Earth system. Humans are fundamentally altering the Earth system through processes with potentially catastrophic consequences, such as anthropogenic climate change, ocean acidification, biodiversity loss, mass extinction, and environmental degradation. Thus, the Anthropocene is often employed as an ethical and critical concept, in order to prompt critical reflection on the relationship that humans have to their environment. Three sites of critical reflection are examined in this entry: the Anthropocene as a diagnosis and prognosis of our ecological predicament; ethics and politics in the Anthropocene; and the Anthropocene and the “End of Nature.”